Water economy of Neotropical savanna trees: Six paradigms revisited - Goldstein, Guillermo Hernan (2008)
Biologists have long been puzzled by the striking morphological and anatomical characteristics of Neotropical savanna trees which have large scleromorphic leaves, allocate more than half of their total biomass to belowground structures and produce new leaves during the peak of the dry season. Based on results of ongoing interdisciplinary projects in the savannas of central Brazil (cerrado), we reassessed the validity of six paradigms to account for the water economy of savanna vegetation. (1) All savanna woody species are similar in their ability to take up water from deep soil layers where its availability is relatively constant throughout the year. (2) There is no substantial competition between grasses and trees for water resources during the dry season because grasses exclusively explore upper soil layers, whereas trees access water in deeper soil layers. (3) Tree species have access to abundant groundwater, their stomatal control is weak and they tend to transpire freely. (4) Savanna trees experience increased water deficits during the dry season despite their access to deep soil water. (5) Stomatal conductance of savanna species is low at night to prevent nocturnal transpiration, particularly during the dry season. (6) Savanna tree species can be classified into functional groups according to leaf phenology. We evaluated each paradigm and found differences in the patterns of water uptake between deciduous and evergreen tree species, as well as among evergreen tree species, that have implications for regulation of tree water balance. The absence of resource interactions between herbaceous and woody plants is refuted by our observation that herbaceous plants use water from deep soil layers that is released by deep-rooted trees into the upper soil layer. We obtained evidence of strong stomatal control of transpiration and show that most species exhibit homeostasis in maximum water deficit, with midday water potentials being almost identical in the wet and dry seasons. Although stomatal control is strong during the day, nocturnal transpiration is high during the dry season. Our comparative studies showed that the grouping of species into functional categories is somewhat arbitrary and that ranking species along continuous functional axes better represents the ecological complexity of adaptations of cerrado woody species to their seasonal environment.